A Practical Guide on Behaviour Change Support for Self-Managing Chronic Disease - Guerreiro, Mara Pereira; Brito Félix, Isa; Moreira Marques, Marta (Springer Nature, 2023)
This open access book is a valuable resource for students in health and other professions and practicing professionals interested in supporting effective change in self-management behaviors in chronic disease, such as medication taking, physical activity and healthy eating. Developed under the auspices of the Train4Health project, funded by the Erasmus+ program of the European Union, the book contains six chapters written by international contributors from different disciplines. Chapter one introduces the competencies necessary for delivering effective behavior change support, based on an established program of work, and related learning outcomes. The four following chapters describe how these competencies can be acquired, focusing on concepts and theories, assessing self-management behaviors, implementing change strategies and person-centered communication, using a practical approach. The last chapter points out supplementary learning resources, developed as part of the Train4Health project.